A flagellin-adjuvanted PED subunit vaccine improved protective efficiency against PEDV variant challenge in pigs. Issue 29 (5th July 2018) - Li, Qianniu; Xu, Zhichao; Wu, Tingting; Peng, Ouyang; Huang, Licheng; Zhang, Yun; Xue, Chunyi; Wen, Zhifen; Zhou, Qingfeng; Cao, Yongchang
Highlights: To meet the pressing need of safe and cost-efficient PED maternal vaccines against PEDV variant, we had reported a promising flagellin-adjuvanted PED subunit vaccine defined as rSF-COE-3D before. In this study, growing piglets were vaccinated with rSF-COE-3D by injection at Houhai acupoint. As expected, rSF-COE-3D significant improved systemic humoral, local mucosal and T cell immune responses in pigs. With improved IgA, neutralizing antibody production and cytokines, rSF-COE-3D offered a better protection against the challenge of a highly pathogenic PEDV variant. Improved protective efficiency of rSF-COE-3D compared with COE was mostly corrected with the increased titters of serum IgA antibody, mucosal IgA antibody in feces and serum neutralizing antibody titers. It offered new messages into the designation of other inefficient maternal vaccine that expects boosted neutralizing antibody and IgA production. Abstract: PEDV variants, causing severe diarrhea in neonatal suckling piglets with a mortality rate up to 100%, have being epidemic since late 2010 in china. To meet the pressing need of safe and cost-efficient PED maternal vaccines against PEDV variant, we vaccinated growing piglets with a flagellin-adjuvanted PED vaccine rSF-COE-3D by injection at Houhai acupoint. The vaccination not only enhanced the antibody responses of serum IgG/IgA, mucosal IgA and serum neutralizing antibody, but also improved the production of IFN-γ and IL-4. Moreover, rSF-COE-3D could provide a better protection against the challenge of a high pathogenic PEDV variant, with less diarrhea pigs, less pigs with detectable PEDV shed, lower rank values of feces and less apparent lesions and inflammation in duodenum of the PEDV infected pigs. The improved protective efficiency of rSF-COE-3D compared with COE was mostly benefited from the enhanced production of serum IgA, mucosal IgA in feces and serum neutralizing antibody titers. Taken together, our data suggest that rSF-COE-3D would be a novel efficient PED vaccine.